PENGARUH CORPORATE GOVERNANCE, LOAN TO DEPOSIT RATIO, NON PERFORMING LOAN, INFLASI DAN KURS TERHADAP KINERJA KEUANGAN PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PADA TAHUN 2007 – 2010 - Fahruri, Arief (www.bsi.ac.id, 2017)
ABSTRACT The objective of this research is to examine the effect of corporate governance mechanisms (the size of independent commissioners and audit committee), loan to deposit ratio, non performing loans, inflation and exchange rate on financial performance of banks listed on the Indonesia Stock Exchange during 2007-2010. A sample of 26 banks is used in this study. Moreover, a multiple regression based on the ordinary least square method is employed. The result shows that, based on the t-test, audit committee and loan to deposit ratio significantly affect bank financial performance (measured by net interest margin). However, independent commissioners, non performing loans, inflation and exchange rate do not have a significant effect. Nevertheless, based on the F-test, all independent variables significantly influence bank financial performance. Keyword : independent commissioners, audit committee, loan to deposit ratio, non performing loan,inflation, exchange rate bank financial performance, net interest margin.